2002
DOI: 10.1164/rccm.2111031
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy with Galectin-3 Inhibits Bronchial Obstruction and Inflammation in Antigen-challenged Rats through Interleukin-5 Gene Downregulation

Abstract: The pathophysiology of asthma involves an intricate network of molecular and cellular interactions. Elevated Th2 cytokines (interleukin [IL]-5 and IL-4) associated with eosinophilic inflammation characterize allergic diseases and provide potential targets for immunomodulation. Recent evidence has demonstrated that galectin-3 induces selective downregulation of IL-5 gene expression in several cell types (eosinophils, T cell lines, and antigen specific T cells). Accordingly, we sought to elucidate whether in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 49 publications
0
41
2
Order By: Relevance
“…53 The findings demonstrate that application of pharmacological concentrations of a galectin-3-expression construct to the airway epithelial surface can have suppressive effects on airway responses that are clearly different from the potentiative role of physiological concentrations of this protein as suggested by the present studies. It is also to be noted that galectin-3 has been shown to inhibit the production of IL-5 in eosinophils and T cells, 54 and thus can potentially down-regulate eosinophil response, because IL-5 can enhance eosinophil maturation.…”
Section: Discussioncontrasting
confidence: 46%
“…53 The findings demonstrate that application of pharmacological concentrations of a galectin-3-expression construct to the airway epithelial surface can have suppressive effects on airway responses that are clearly different from the potentiative role of physiological concentrations of this protein as suggested by the present studies. It is also to be noted that galectin-3 has been shown to inhibit the production of IL-5 in eosinophils and T cells, 54 and thus can potentially down-regulate eosinophil response, because IL-5 can enhance eosinophil maturation.…”
Section: Discussioncontrasting
confidence: 46%
“…Although both galectin-3 and galectin-1 bind to T cells to trigger T cell death, we show here that the galectins differ with respect to cell surface receptors, receptor localization after binding, and requirements for specific receptors to trigger T cell death. Although administration of both galectin-3 and galectin-1 were immunosuppressive in several animal models of inflammatory disease, and both galectin-3 and galectin-1 influence the threshold of TCR signaling (58,59), galectin-1 treatment reduces Th1-type cytokine production (5, 32, 60), while galectin-3 treatment reduces Th2-type cytokine production (33,61). Moreover, galectin-3 and galectin-1 knockout mice have distinct phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that galectin-3 is mitogenic for cardiac fibroblasts, induces collagen deposition and may lead to ventricular dysfunction [25]. In the lung, epithelial expression of galectin-3 is increased in nonsmall lung cancer [26,27], while in murine asthma models, gene therapy targeted to galectin-3 inhibits allergen-induced airway inflammation, including IL-5 expression, and epithelial mucous metaplasia [28][29][30]. Secretion of galectin-3 is also upregulated in a rat model of radiation-induced lung fibrosis [31,32].…”
Section: Discussionmentioning
confidence: 99%